Comparative study of dissection of Calot’s triangle and gallbladder using monopolar hook versus harmonic scalpel in laparoscopic cholecystectomy - Modi, Naresh A.; Ray, M. S.; Thakore, Digpal H.; Panchal, Brinda B.; A. Raval, Aditya; A. Patel , Vishal (International Surgery Journal, 2023)
Background: Laparoscopic cholecystectomy (LC) using surgical electrocautery is considered to be the gold standard procedure for the treatment of uncomplicated cholecystitis and cholelithiasis. The objective of the current study was to evaluate the effectiveness and safety of the Harmonic scalpel, an advanced laparoscopic technique when compared to electrocautery. Methods: From June, 2021 through December 2022, a total of 50 patients were randomly allocated to LC with a harmonic scalpel (group 2, 25 patients) or conventional monopolar electrocautery (group 1, 25 patients). The main outcome measures were gall bladder perforation during surgery (bile leakage), stone spillage, duration of surgery, hospital stay. Results: The 2 groups were comparable with respect to baseline patient characteristics. When compared to conventional monopolar electrocautery, Gall bladder perforation during surgery (bile leakage) 12% vs. 8%, stone spillage 4% vs. 8%, duration of surgery 52.13 min vs. 54.89 min, hospital stay 2.09 days vs. 2.04 days. Conclusions: LC using conventional monopolar electrocautery is as effective and safe as that with the harmonic scalpel, for treating uncomplicated cholecystitis and cholelithiasis.